2010
DOI: 10.2166/wst.2010.480
|View full text |Cite
|
Sign up to set email alerts
|

CFD modelling of flow field and particle tracking in a hydrodynamic stormwater separator

Abstract: The best management practices (BMPs) for control of urban stormwater pollution are evaluated to remove solid particles containing various pollutants. Currently, most storm runoff treatment devices using primary pollutant removal mechanism are applied to storm water since most pollutants in runoff are associated with the solid particulates. A hydrodynamic separator is a storm water treatment device using centrifugal motion which separates solids pollution from runoff. In this study, the velocity flow field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…If the user knows which particle size fractions have better removal, the analyses of performance of the HD unit would be more specific and probably yielded precise results. The results obtained by Lee et al (2010) using computational fluid dynamics (CFD) are very similar to the simple analysis done in this study; particles smaller than 100 [im are poorly removed. Sediment Removal by Detention Basin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…If the user knows which particle size fractions have better removal, the analyses of performance of the HD unit would be more specific and probably yielded precise results. The results obtained by Lee et al (2010) using computational fluid dynamics (CFD) are very similar to the simple analysis done in this study; particles smaller than 100 [im are poorly removed. Sediment Removal by Detention Basin.…”
Section: Discussionsupporting
confidence: 75%
“…HD design varies among vendors, which may be one of the reasons that these devices have no statistical significant differences between the median of average influent and effluent (Figure 1) as reported to the International BMP Database. Lee et al (2010) performed extensive testing of the performance of a HD unit (different than the one used in this study) and observed that the suspended solids removal was inversely proportional to the surface loading rate (usually called surface overflow rate). This observation is a characteristic of sedimentation devices, and they concluded that gravity was a significant process in the removal of particles in the HD unit.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with the design criteria of these systems, the MTS appears to effectively be designed based on OFR albeit with a slightly optimistic expected performance when compared to results from this study that the overall mass removal under all load conditions tested was slightly over 92%. Moreover, performance data shows a contradictory picture: a design criterion of 95% removal of particles 75 µm but observed removal rates for particle sizes below 212 μm consistently below expectations [10]. On the other hand, there is an evident discrepancy between design criteria and OFR for the FVS and the overall observed mass removal of around 85% would suggest neither OFR nor design criteria accurately predict actual performance, even after considering that the contribution of particles smaller than 106 μm to the total mass load was between 3 and 4% (Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…The efficacy of CFD in urban drainage-related applications has been articulated by Ta (1999), Faram & Harwood (2000), and Harwood (2006), who collectively substantiate the compatibility and advantages of CFD simulation for the design and analysis of UDSs. Notably, Lee et al (2010) leveraged CFD technology to rigorously assess the performance of a hydrodynamic stormwater separator, with a particular emphasis on the impact of underflow on the separator's efficacy. Similarly, Peng et al (2019) adeptly employed CFD simulations to scrutinize the influence of various geometric ratios of separator diameter to height on sediment removal rates, thereby enhancing the understanding of the underlying fluid dynamics and facilitating the informed design of such separators.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%